Real‐time in vitro intravascular reconstruction and navigation for endovascular aortic stent grafting. Issue 4 (9th February 2016) - Shi, Chaoyang; Tercero, Carlos; Wu, Xianliang; Ikeda, Seiichi; Komori, Kimihiro; Yamamoto, Kiyohito; Arai, Fumihito; Fukuda, Toshio
Abstract: Background: Trans‐catheter endovascular stent grafting minimizes trauma and increases the benefitting patient population. However, the alignment between stent graft branches and vasculature branches remains time‐consuming and challenging, and such techniques require a significant amount of contrast agent for imaging. Methods: A new framework for intravascular reconstruction based on sensor fusion between intravascular ultrasound (IVUS) imaging and electromagnetic (EM) tracking was proposed. A new image processing method was presented to realize fully automatic processing of IVUS imaging and 3D reconstruction in real time, as well as branch detection for alignment and deployment. Complementary navigation using CT data allows for efficient catheter advancement and assistant clinical judgement. Results: The reconstruction of an in vitro descending aorta phantom with branches was realized at 35 Hz, with cross‐section radius average error of 0.64 mm. Conclusion: The proposed method demonstrates significant potential for clinical applications, enables navigation for precise alignment and placement for stent grafting to reduce surgical time, and decreases hemorrhagic collisions and the use of contrast agent. Copyright © 2016 John Wiley & Sons, Ltd.